Thinkercise: An educational VR game for Python programming - Thirada Theethum; Attawut Arpornrat; Sirion Vittayakorn (My University, 2021)
Thinkercise was developed to be an educational VR game for reviewing knowledge and skills in Python programming. The game not only encourages players to move their physical body during the gameplay but also prompts players to use their basic Python programming knowledge and skill to complete a task in the game. In the gameplay, players are required to answer a series of programming related questions by moving their body in various ways in a limited time, such as punching a target, or avoiding an obstacle. To achieve the maximum score, players need to hit the correct answer targets at the right time as well as to avoid all obstacles in the game successfully. Experimental results demonstrate that our game helps increase the students' performance in computer programming by 40.8%. It outperformed self-learning by 30%.
Keywords: Educational Games and Gamification; Virtual Reality Applications and Impacts; Teaching and Learning Programming